Conservation Comprehensive Approach: Study on Exploration, Habitat Analysis, Propagation, and Reintroduction of the Indonesian Endemic Endangered Titan Arum (Amorphophallus titanum Becc.) - Setiawan, Ryan Budi; Yusniwati, Yusniwati; Rahma Wati, Dela; Purnama Sari, Indah; Rahmah, Siti; Haryanti, Sindi; Arief Laksana Bosma, Pandu (Jurnal Manajemen Hutan Tropika, 2025)
Titan arum (Amorphophallus titanum Becc.) is an endemic species of Indonesia that is found naturally only in Sumatra and is classified as endangered, with an estimated 303 mature individuals remaining in their natural habitat. The population is decreasing due to deforestation, tuber exploitation, long flowering times, and protandry. Therefore, both in-situ and ex-situ conservation programs are necessary to preserve this species. The research aims to explore natural populations, analyze habitat conditions, develop propagation methods, and conduct reintroduction efforts to support the conservation of A. titanum. This study was conducted from 2023 to 2024 in Palupuah, Agam Regency, the Agriculture Faculty of Universitas Andalas, and several locations for the reintroduction of A. titanum. The research found that A. titanum habitat consists of forests rich in humus and litter, as well as banana cultivation areas. During the exploration, 7 individuals were identified: one in dormancy, one fruiting, and 5 in the vegetative phase. Seed germination experiments categorized seeds into seven classes based on their weight. The most dominant seed class weighed between 2.9 g and 3.2 g, comprising 38 seeds or 26.9% of the total. The germination rate and seedling growth were high, as all seeds exhibited 100% and produced seedlings of relatively uniform size. Propagation was carried out using in vitro culture techniques with petiole explants. The results showed that 2 mg L-1 benzyl aminopurine (BAP) successfully induced callus formation with a 100% induction rate, while a concentration of 1.5 mg L-1 achieved the highest shoot induction rate at 58.3%, with an average of 1.3 shoots and 7.9 roots per explant. The propagated seedlings were subsequently replanted in several locations for reintroduction activities.